HOTS Question Analysis in Elementary Mathematics: Focus on Fractions, Geometry, and Comparison Topics in 6th Grade - Rizki Rahmali Fadhillah; Erza Mulia Agustin; Astrid Ramadhanti; Jesi Alexander Alim; Muhammad Fendrik (Research, Training and Philanthropy Institution Natural Aceh, 2026)
This study aims to determine the mathematical ability of sixth-grade students in solving Higher Order Thinking Skills (HOTS) type mathematics problems. This study is a descriptive qualitative study. The study's subjects were sixth-grade students from 3 elementary schools in Pekanbaru City. The methods used in this study include tests, interviews, and documentation. The test consisted of 15 HOTS-type mathematics verification questions. The test results were then explained and supported by interviews and student documentation. The results showed that students' abilities to solve HOTS mathematics problems across three schools differed significantly. Category A schools had an average score of 49.5, which was in the high category. Category B schools (average 20.0, medium category) and Category C schools (average 17.6) showed abilities in Fractions, Geometry, and Comparison that were in the low category. From these results, it can be seen that students have different abilities in solving problems. From the perspective of problem description and solution, students have not fully used concepts and procedures to formulate and solve problems. From a communication perspective, students have not fully written their answers coherently or provided a solution to the problem.